If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1 + 2x) + 5 = (x + 6) (1 * 4 + 2x * 4) + 5 = (x + 6) (4 + 8x) + 5 = (x + 6) Reorder the terms: 4 + 5 + 8x = (x + 6) Combine like terms: 4 + 5 = 9 9 + 8x = (x + 6) Reorder the terms: 9 + 8x = (6 + x) Remove parenthesis around (6 + x) 9 + 8x = 6 + x Solving 9 + 8x = 6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9 + 8x + -1x = 6 + x + -1x Combine like terms: 8x + -1x = 7x 9 + 7x = 6 + x + -1x Combine like terms: x + -1x = 0 9 + 7x = 6 + 0 9 + 7x = 6 Add '-9' to each side of the equation. 9 + -9 + 7x = 6 + -9 Combine like terms: 9 + -9 = 0 0 + 7x = 6 + -9 7x = 6 + -9 Combine like terms: 6 + -9 = -3 7x = -3 Divide each side by '7'. x = -0.4285714286 Simplifying x = -0.4285714286
| -(5x^4-36x^2)*0.25=0 | | 10z+8z+2=12z+9z+5 | | -5x^4+36x^2=0 | | 5x^2-5x-2=0 | | x^3-12x^2+36x=0 | | 12x+108=96 | | x^2+10x+21= | | x+18+4x=-11-4x-16 | | .333x+8=x+10 | | x^2-8x-16=23 | | .5x+8=x+10 | | 3x+51= | | x^2=500 | | 43+2x=32 | | 3(3)+5(4)=29 | | 6x-43=3x-10 | | 93+4=[17-(2+3)] | | 4x-7=3.5+x | | 6x^2+15=0 | | 4Y^2+3Y-10=0 | | -18x-30=6 | | 3x+5y=29 | | 82-4x=23x+16 | | 12-7x=111-28x | | -6c+9=-4c-3 | | 6x+5=-79-8x | | 6x^2+37x-35=0 | | -2x=7x-18 | | 2x^2+15=0 | | 4(2c-3)-3(c-4)= | | 80Y^2-210Y-245=0 | | y=-2.5x+4 |